The GLAM airborne campaign across the Mediterranean Basin - Ricaud, Philippe; Zbinden, Régina; Catoire, Valéry; Brocchi, Vanessa; Dulac, François; Hamonou, Eric; Canonici, Jean-Christophe; El Amraoui, Laaziz; Massart, Sébastien; Piguet, Bruno; Dayan, Uri; Nabat, Pierre; et al. (My University, 2018)
The Gradient in Longitude of Atmospheric Constituents above the Mediterranean Basin (GLAM) 2014 airborne campaign performed original in situ observations of gases and aerosols across the Mediterranean troposphere, which, combined with satellite measurements and model outputs, highlight their summertime variability.
Keywords: Earth atmosphere; Meteorology; Atmospheric constituents; In-situ observations; Mediterranean basin; Satellite measurements; Atmospheric aerosols